MOBILE SUBRETINAL CYSTICERCUS IMAGED BY SPECTRAL-DOMAIN OPTICAL COHERENCE TOMOGRAPHY WITH MOTION TRACKER. Issue Volume 12:Issues 4(2018) (2018) - Bypareddy, Ravi; Takkar, Brijesh; Chawla, Rohan; Sachdeva, Neha; Azad, Shorya V.; Tripathy, Koushik
Abstract : Purpose: To report optical coherence tomography–based videoimaging of alive subretinal cysticercus along with its mobile scolex. Methods: Spectral-domain optical coherence tomography was used to record high-definition videoimages, using the inbuilt motion tracker, in a 12-year-old boy with history of neurocysticercosis. Result: The scolex was found to be sensitive to light, and contractile movements were seen in the cyst wall and the germinative layers. The patient underwent vitrectomy, and the diagnoses were confirmed with histopathologic assessment. Conclusion: Optical coherence tomography is a useful tool for diagnosing posterior segment cysticercosis. The intense motion of scolex does not impact the surrounding ocular structures. Abstract : Optical coherence tomography is a useful tool for diagnosing posterior segment cysticercosis. The intense motion of scolex does not impact the surrounding ocular structures.Supplemental Digital Content is Available in the Text.